2016
DOI: 10.1111/1462-2920.13515
|View full text |Cite
|
Sign up to set email alerts
|

MoRad6‐mediated ubiquitination pathways are essential for development and pathogenicity inMagnaporthe oryzae

Abstract: The ubiquitin system modulates protein functions through targeting substrates for ubiquitination. Here, E2 conjugating enzyme MoRad6-related ubiquitination pathways are identified and analyzed in Magnaporthe oryzae, the causal agent of rice blast disease. Disruption of MoRad6 leads to severe defects in growth, sporulation, conidial germination, appressorium formation, and plant infection. To depict the functions of MoRad6, three putative ubiquitin ligases, MoRad18, MoBre1 and MoUbr1, are also characterized. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 64 publications
3
26
0
Order By: Relevance
“…Post-translational modification by ubiquitin is essential for regulation of protein abundance and function. Previous studies have revealed importance of the ubiquitin system in the model plant pathogenic fungus M. oryzae ( McCafferty and Talbot, 1998 ; Oh et al, 2012 ; Prakash et al, 2016 ; Shi et al, 2016 ). However, little has been addressed on the deubiquitination process.…”
Section: Discussionmentioning
confidence: 99%
“…Post-translational modification by ubiquitin is essential for regulation of protein abundance and function. Previous studies have revealed importance of the ubiquitin system in the model plant pathogenic fungus M. oryzae ( McCafferty and Talbot, 1998 ; Oh et al, 2012 ; Prakash et al, 2016 ; Shi et al, 2016 ). However, little has been addressed on the deubiquitination process.…”
Section: Discussionmentioning
confidence: 99%
“…To test whether MoGrp1 contributes to intron splicing, two genes, MST7 and MoRAD6, which are important to fungal growth, conidiation, and pathogenicity in M. oryzae (Zhao et al 2005;Shi et al 2016a), were selected for analysis. The intron splicing efficiency was evaluated by RT-PCR with a pair of primers amplifying the intron region.…”
Section: Mogrp1 Is Necessary For Normal Splicing Of Genes Involved Inmentioning
confidence: 99%
“…Recent evidence has shown that conidial germination is delayed by a proteasome inhibitor Bertomzib, indicating that the ubiquitin system plays a critical role in triggering germination (Oh et al ., ). Our previous results identified an RING‐type ubiquitin ligase MoUbr1 involved in activating conidial germination (Shi et al ., ). In this study, we found that Δ Mofbx15 , Δ Mocdc4 and Δ Mofwd1 also displayed obvious germination defects in different degrees, with Δ Mofwd1 the most severe, suggesting that conidial germination is regulated by a complex network in which the ubiquitin system components take part.…”
Section: Discussionmentioning
confidence: 97%
“…The expression of MoFrq was monitored by qPCR. Protein extraction and western blotting were performed as previously described (Shi et al, 2016).…”
Section: Fluorescent-microscopy Observationmentioning
confidence: 99%